CircRNA circ-ATAD1 suppresses miR-618 maturation to participate in colorectal cancer - Li Cao; Guanglong Dong; Huan Li (BMC Gastroenterology, 2022)
Abstract Background CircRNA circ-ATAD1 has been characterized as an oncogenic circRNA in gastric cancer, while its role in colorectal cancer (CRC) is unknown. This study was carried out to explore the role of circ-ATAD1 in CRC. Methods Paired CRC and adjacent non-tumor tissue samples collected from 64 CRC patients were subjected to RNA extractions and RT-qPCRs to analyze the expression of circ-ATAD1, premature miR-618, and mature miR-618 in CRC. The effects of circ-ATAD1 overexpression on miR-618 maturation were analyzed by transfecting circ-ATAD1 expression vector into CRC cells, followed by determining the expression of premature miR-618 and mature miR-618 using RT-qPCR. The subcellular location of circ-ATAD1 was analyzed by nuclear fractionation assay, and the interaction between circ-ATAD1 and premature miR-618 was analyzed by RNA pull-down assay. The roles of circ-ATAD1, premature miR-618, and mature miR-618 in regulating CRC cell proliferation were explored by CCK-8 assay. Results Circ-ATAD1 was upregulated in CRC and predicted poor survival. In addition, circ-ATAD1 was inversely correlated with mature miR-618 but not premature miR-618. In CRC cells, circ-ATAD1 overexpression decreased the level of mature miR-618 but not premature miR-618. Circ-ATAD1 was detected in both the nucleus and cytoplasm. A direct interaction between circ-ATAD1 and miR-618 was observed. Moreover, circ-ATAD1 overexpression reduced the inhibitory effects of miR-618 overexpression on cell proliferation. Conclusion Circ-ATAD1 is overexpressed in CRC and may suppress miR-618 maturation to participate in CRC.